Implementasi Certainty Factor Untuk Diagnosis Penyakit dan Hama Pada Pelepah dan Daun Kelapa Sawit Beserta Penanganannya - Beni Frandian; Ilka Zufria; Muhammad Dedi Irawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Oil palm (Elaeis guinensis) is a plant that has its own charm and plays an important role in people's lives. Plants are categorized as normal if they can process their physiological functions properly. In line with the development and expansion of community-owned oil palm land areas, more and more problems arise due to various types of diseases and pests attack on oil palm plants, especially on the midrib and leaves of oil palm. The existence of diseases and pests that cause losses in plant productivity also results in loss of costs used to restore plants that have been attacked by diseases or pests in nurseries, immature and mature plants. The lack of understanding of farmers regarding how to diagnose and proper control of oil palm diseases and pests as well as the availability of experts or experts in the field of oil palm in smallholder oil palm plantation areas can be overcome by presenting experts or experts or doubling the knowledge possessed by experts in the coconut field. oil palm by building an expert system for the diagnosis of diseases and pests in oil palm leaf midribs. The certainty factor method is used to describe the uncertainty in thinking and express the degree of confidence of the expert or expert in diagnosing the types of diseases and pests of oil palm. The developed expert system is expected to be useful for farmers in the area or ordinary people in diagnosing diseases and pests on oil palm leaf sheaths through the symptoms selected during consultations to diagnose the types of diseases and pests that are being experienced.